Daring to Win : Special Forces at War - Eshel, David (GHQ, Rawalpindi Army Education Publishing House, 2003)
Sometimes, the outcome of a war depends upon special forces with the skills and the daring to go beyond the call of duty$1 (Band undertake especially dangerous assignments. Dividing his accounts into commando raids, air and seaborne actions, and postwar elite missions, author David Eshel$1 (Bhimself a retired officer in the Israeli military$1 (Bcharts 39 events where special forces have played a crucial role. They range from the "bridge too far" at Arnhem to the audacious raid at Entebbe, and include early storm troopers in World War One, the Dambuster bombers, and underwater warriors. It will make clandestine operations just a little less secret.s
Include Illustrations, Maps and Index.
Keywords: Special forces (Military science) -- Military history, Modern -- Military history, Modern -- 20th century